Daur Ulang Koran Bekas - Triyanto Hadisoemarto (Balai Besar Kimia dan Kemasan, 2001)
Old newspaper (ONP) is a potential secondary fibre resource, especially for newsprint production, which can be used either in combine with virgin pulp or 100% recycled furnish.Though there are a number of factors that must be considered in recycling ONP, but it offers significant cost advantages compared with virgin pulp production. It's unfortunate that methods for evaluating de inking performance are not well defined.